2023
DOI: 10.1002/adfm.202311160
|View full text |Cite
|
Sign up to set email alerts
|

Superior Energy Storage Performance in Antiferroelectric Epitaxial Thin Films via Structural Heterogeneity and Orientation Control

Tianfu Zhang,
Yangyang Si,
Shiqing Deng
et al.

Abstract: Dielectric capacitors are desired for electronics and electrical power systems because of their fast charge–discharge speed and high‐power density. Nevertheless, dielectric capacitors typically exhibit lower energy densities in comparison to other energy storage systems like batteries or fuel cells. Among dielectrics, antiferroelectrics have shown great promise for high energy density because of their characteristic double hysteresis loops. However, current antiferroelectric capacitors still face challenges of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…On the other hand, reducing the difference between E AF and E FA , i.e., reducing electric hysteresis, can decrease the hysteresis area, that is, reduce the energy loss density J loss and increase the energy storage efficiency. Previous studies have demonstrated that introducing nanoscale structural heterogeneity into AFEs generally via chemical doping is an effective approach to lower the energy barrier between the AFE and field-driven FE phases and thus reduce the electric hysteresis [157,[292][293][294]. Increasing saturation polarization or decreasing remnant polarization.…”
Section: Energy-storage Capacitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, reducing the difference between E AF and E FA , i.e., reducing electric hysteresis, can decrease the hysteresis area, that is, reduce the energy loss density J loss and increase the energy storage efficiency. Previous studies have demonstrated that introducing nanoscale structural heterogeneity into AFEs generally via chemical doping is an effective approach to lower the energy barrier between the AFE and field-driven FE phases and thus reduce the electric hysteresis [157,[292][293][294]. Increasing saturation polarization or decreasing remnant polarization.…”
Section: Energy-storage Capacitorsmentioning
confidence: 99%
“…For instance, Zhang et al [294] demonstrated that the combination of structure heterogeneity and orientation control in relaxor AFE (Pb 0.97 La 0.02 )(Zr 0.55 Sn 0.45 )O 3 thin films can simultaneously achieve high energy storage efficiency (~98.5 %) and energy storage density (~84.45 J/cm 3 ). In that work, introducing La 3+ and Sn 4+ dopants into AFE PbZrO 3 can engineer the structural heterogeneity and disrupt the long-range ordered AFE domains, which can effectively decrease the polarization hysteresis (E AF -E FA ) [294]. By controlling the orientation, the (1 1 1)-oriented films exhibit the largest polarization among (1 1 1)-, (1 1 0)-and (0 0 1)-oriented films and gain the highest energy storage density (~84.45 J/cm 3 ) [294].…”
Section: Energy-storage Capacitorsmentioning
confidence: 99%
See 1 more Smart Citation